Correction Factors for δ18O-Derived Global Sea Surface Temperature Reconstructions From Diagenetically Altered Intervals of Coral Skeletal Density Banding - Sivaguru, Mayandi; Fouke, Kyle W.; Todorov, Lauren; Kingsford, Michael J.; Fouke, Kaitlyn E.; Trop, Jeffrey M.; Fouke, Bruce W. (Frontiers in Marine Science, 2019)
Reconstruction of sea surface temperature (SST) from the 18O and Sr/Ca composition of coral skeletal density banding (CSDB), identified with x-ray diffraction and micro computed tomography, provides invaluable centuries-long records of ocean circulation and climate change. Comparison with age-equivalent instrument measurements of SST over the last 125 years has proven these 18O-derived SST reconstructions to be generally reliable. However, notable exceptions occur within discrete CSDB stratigraphic intervals that yield 18O-derived SST underestimates of as much as 9oC with respect to instrument measured SST. Here we combine high-resolution optical and electron microscopy with geochemical modeling to establish correction factors for the impact of marine seafloor physical, chemical, and biological alteration (diagenesis) within these altered intervals of CSDB stratigraphy. Four cores were collected from Porites coral heads across a 4-24 m water depth bathymetric transect at Myrmidon Reef, Great Barrier Reef, Australia. Precise mapping of diagenetic aragonite cementation was completed within CSDB patterns digitally overlaid on 35 petrographic thin sections fully covering 2.1 m of core. The vast majority of core skeletal material exhibited little to no diagenetic aragonite cementation. However, extensive diagenetic alteration was observed within discrete CSDB intervals near the base of the two deeper water Porites heads. This diagenesis serves to modify skeletal density and CSDB stratigraphy in these intervals, as well as structurally reinforce the coral skeleton. Reliable 18O-based SST correction factors for these diagenetically altered CSDB intervals are established here by applying the percent mixing of diagenetic aragonite cement to a binary mixing model. This approach, with quantitative extents of mixing established with both microscopy and existing globally distributed coral 18O and Sr/Ca data sets, accurately restores modern and fossil coral 18O-derived SST records. Results indicate that as little as 5% mixing of diagenetic aragonite cement with original coral skeleton will cause 18O-based SST anomalies of 0.9oC.